Analisis Risiko pada UKM Tahu Takwa Kediri terhadap Dampak Pandemi COVID-19 - Imam Safi'i; Silvi Rushanti Widodo; Ria Lestari Pangastuti (Universitas Katolik Parahyangan, 2020)
The Pandemic of COVID-19 and social restriction policy (PSBB) in Indonesia caused a lot of impacts, one of them is Tofu Takwa SMEs in Kediri. This condition disrupts production activities up to marketing. Then it takes a risk analysis by looking at the main potential risks that arise while pandemic like this and do manage to get a strategy for their business sustainability. This research aims to analyze and manage the main risks that occur in Tofu Takwa SMEs in Kediri. The results showed that there are 3 risks in a high level like decrease of the income, decrease in production amount and increase the price of raw materials and 1 risk in middle level like late in delivery raw material so that it can be done by financial strategy, resize, search for a new market with social media and cooperate with the local government to help the marketing of social service programs.